Застосування колориметричного методу неруйнівного контролю в промисловості - Оніщук, Д. А.; Тітов, К. Г. (ХНУРЕ, 2024)
This paper deals with the application of the colometric method of non-destructive testing in industry. This method allows for control and measurement without interfering with the object under study, which makes it an important tool for both quality control and scientific research in industry
Keywords: неруйнівний контроль в промисловості; колориметричний метод